Stalking: the elusive crime - Sheridan, Lorraine (Legal and criminological psychology, 2001)
Purpose. Stalking has given rise to considerable media interest and public concern throughout the 1990s. The England and Wales Protection from Harassment Act 1997 was introduced to legislate against the crime, but failed to define it. This article discusses the difficulties of defining a crime in which the behaviour of perpetrators is often ostensibly innocuous. Arguments. A review of 12 studies reveals that stalkers engage in very similar patterns of activities. Consequently, it may be possible to create guidelines for what does and does not constitute stalking. Next, a simple method of constructing stalker typologies is suggested, the classification being affected by the manner in which stalking is defined. Conclusions. It is suggested that the difficulties inherent in framing anti-stalking legislation may have been overestimated and that existing academic research can provide at least a working definition of the crime, provided that a common system of classifying stalking cases is adopted.